Life History and Immature Stages of the Malay Birdwing Butterfly, Troides amphrysus, and a New Larval Host Plant from Java, Indonesia: Life history, immature stages, and new larval hostplant of the Malay Birdwing butterfly - Shahroni, Abdul Mutholib; Bagyo, Yanuwiadi; Djunijanti, Peggie (Journal of Tropical Life Science, 2026)
Troides amphrysus (Cramer, 1779) is one of the iconic birdwing butterflies widely distributed from the Malay Peninsula to Java, Indonesia. Although this species is widespread, comprehensive information on its immature stages and larval development remains poorly studied. This study aims to document the complete immature stages and analyze the developmental biology of T. amphrysus on Java Island. Observations were conducted in the coastal forests of South Malang, East Java, Indonesia. Between July and December 2023, a two-week field inspection was conducted to collect eggs and larvae (L). Captive rearing of all samples was carried out in the laboratory to measure the life cycle duration and body length. The results showed that the period to complete the immature stage lasted an average of 74.6 days, with the instar L3 being the longest. Larval growth followed a sigmoid pattern, with the most variation occurring at instars L2–L3, indicating a potentially sensitive stage influenced by environmental and genetic factors. The instar head capsule size ranges from 1.0 mm (L1) to 7.0 mm (L5). Additionally, this study reports Aristolochia zollingeriana as a new host plant record for T. amphrysus on Java Island. This finding highlights the importance of conserving coastal forest habitats and host plants of the Aristolochiaceae family to sustain the T. amphrysus population. New insights into developmental biology, the importance of coastal forest habitats, and the ecological availability of larval host plants for T. amphrysus have been highlighted in this study. Thus, it can support conservation strategies to maintain the long-term survival of this protected butterfly species in Java.